Post‐pyloric feeding tube placement in critically ill patients: Extending the scope of practice for Australian dietitians. Issue 1 (4th July 2017) - Yandell, Rosalie; Chapman, Marianne; O'Connor, Stephanie; Shanks, Alison; Lange, Kylie; Deane, Adam
Abstract : Aim: To determine whether the placement of a post‐pyloric feeding tube (PPFT) can be taught safely and effectively to a critical care dietitian. Methods: This is a prospective observational study conducted in an adult intensive care unit (ICU). The intervention consisted of 19 attempts at post‐pyloric intubation by the dietitian. The 10 'learning' attempts were performed by the dietitian under the direction of an experienced (having completed in excess of 50 successful tube placements) user. A subsequent nine 'consolidation' attempts were performed under the responsibility of the intensive care consultant on duty. The primary outcome measures were success (i.e. tip of the PPFT being visible in or distal to the duodenum on X‐ray) and time (minutes) to PPFT placement. Patients were observed for adverse events per standard clinical practice. Results: A total of 19 post‐pyloric tube placements were attempted in 18 patients (52 (23–70) years, ICU admission diagnoses: trauma n = 4; respiratory failure n = 3; and burns, pancreatitis and renal failure n = 2 each). No adverse events occurred. Most (75%) patients were sedated, and mechanically ventilated. Prokinetics were used to assist tube placement in 11% (2/19) of attempts, both of which were successful. Placement of PPFT was successful in 58% (11/19) of attempts. Whilst training, the success rate was 40% (4/10) compared with 78% (7/9) once training was consolidated ( P = 0.17). In the successful attempts, the mean time to placement was 11.0 minutes (3.9–27.1 minutes). Conclusions: A dietitian can be trained to safely and successfully place PPFT in critically ill patients.